The role of dhikr in attaining ma'rifah and tawhid: a hermeneutical approach to Islamic spirituality - Sharif, Dziauddin; Kamarzaman, Mohd Haidhar; Kamaruzaman, Mohd Asyran Safwan; Zulkefli, Ahmad Arif (RSIS International, 2025)
This paper explores the role of dhikr (remembrance of Allah) in attaining ma’rifah (spiritual knowledge) and tawhid (oneness of Allah) through the lens of hermeneutical analysis. Dhikr is not merely a verbal practice in Islam; it is a profound spiritual exercise that connects the heart and mind to Allah. By focusing on key terms such as “هو” (Hu), this study delves into how dhikr transcends simple utterances and serves as a pathway to deeper spiritual awareness. The analysis is structured around four key elements: interpretation of key terms, contextual examination, comparison of scholarly perspectives, and textual integration with Quranic verses and hadiths. Through hermeneutical analysis, this paper uncovers the layers of meaning embedded in dhikr and illustrates how it leads to higher spiritual states and a deeper realization of Allah’s oneness. The findings highlight the importance of sincerity in dhikr and the unique spiritual rewards of remembering Allah without worldly requests.